Economic analysis for the impacts of oil price uncertainty on Chinese and U.S. stock returns before and during the COVID-19 pandemic - Wang, Xiaofan; Xu, Mengdie (Transactions on Economics, Business and Management Research, 2024)
The recent outbreak of COVID-19 has increased uncertainty across financial markets; therefore, examining the influences of oil price uncertainly on stock rewards is of considerable significance in this context. This article applies the crude oil volatility index (OVX) as a synthetic, precise measure of oil price uncertainty to explore how Chinese and U.S. stock returns respond differently to OVX changes prior to and during COVID-19. This issue is addressed by adopting a nonparametric causality-in-quantiles method, which can provide a more robust investigation of nonlinear impacts in various market situations. Our results indicate that stock returns in response to OVX changes across China and the U.S. are heterogeneous around the COVID-19 period. Before the epidemic, Chinese stock returns were considerably less responsive to the OVX shocks compared with the U.S. In contrast, China’s stock returns responded more strongly to OVX changes during the outbreak, while U.S. stock returns reacted in the opposite way.